Long Non-Coding RNAs as Key Modulators of Pancreatic β-Cell Mass and Function - López–Noriega, Livia; Rutter, Guy A. (Frontiers in Endocrinology, 2021)
Numerous studies have sought to decipher the genetic and other mechanisms contributing to β-cell loss and dysfunction in diabetes mellitus. However, we have yet to fully understand the etiology of the disease or to develop satisfactory treatments. Since the majority of diabetes susceptibility loci are mapped to non-coding regions within the genome, understanding the functions of non-coding RNAs in β-cell biology might provide crucial insights into the pathogenesis of type 1 (T1D) and type 2 (T2D) diabetes. During the past decade, numerous studies have indicated that long non-coding RNAs play important roles in the maintenance of β-cell mass and function. Indeed, lncRNAs have been shown to be involved in controlling β-cell proliferation during development and/or β-cell compensation in response to hyperglycaemia. LncRNAs such as TUG-1 and MEG3 play a role in both β-cell apoptosis and function, while others sensitize β-cells to apoptosis in response to stress signals. In addition, several long non-coding RNAs have been shown to regulate the expression of β-cell-enriched transcription factors in cis or in trans. In this review, we provide an overview of the roles of lncRNAs in maintaining β-function and mass, and discuss their relevance in the development of diabetes.